The Influence of Weekly Training Load on Match Physical Demands in Spanish Professional Soccer Players: A Full In-Season Study - José C. Ponce-Bordón; Jorge Polo-Tejada; David Lobo-Triviño; Borja Sanabria-Pino; Javier Raya-González; Alberto Muñoz; Tomás García-Calvo (Sensors)
This study aimed (i) to analyze the relationship between weekly accumulated training load (TL) and match physical demands in the same week and (ii) to describe the training/match ratios of different external load measures considering variations across different training days. Twenty-one Spanish male professional soccer players were involved in the study. Total distance (TD), medium speed running (MSR, distance 10.8–18.0 km·h−1), high-speed running (HSR, >21 km·h−1), very high-speed running (VHSR, 18.0–25.2 km·h−1), sprinting-speed running distance (Sprint, >25.2 km·h−1), player load (PL), number of accelerations (ACC), and decelerations (DEC) were recorded during training sessions and matches using 10 Hz GPS devices. Correlations between the weekly TL and match physical demands were trivial and negative for TD (r = −0.08) and PL (r = −0.05); trivial and positive for MSR (r = 0.02), HSR (r = 0.07), Sprint (r = 0.09), and DEC (r = 0.06); and small and positive for VHSR (r = 0.22) and ACC (r = 0.19). The greatest TD, MSR, VHSR, Sprint, HSR, and PL values and their derivate ratios occurred in MD–3. The present study highlights the need for soccer athletes to be exposed to similar demands to those observed during matches.